Analysis Of Communication And Hr Implementation Of The Covid-19 Vaccination Program In The Elderly In North Musi Rawas District - Sanggam Magda Lasmaria Siahaan; Kamson Pasaribu (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The purpose of this study was to study the differences in the use of the ulos type in the mangosteen holi tradition in the understanding of the Batak ethnic community in Aek Sopang Humbang Habinsaran. Even though the Aek Sopang Batak ethnic community is part of the Toba Batak ethnic group in general, in the Mangongkal Holi tradition they have differences in wearing ulos cloth on the excavated bones. Research in this study was conducted using qualitative methods with data collection techniques through literature review, field observations and interviews. The qualitative method was carried out so that the researcher understands the experience of the Batak people in Aek sopang regarding the type of ulos which is used differently in other areas of the Toba community in the mangongkal holi tradition. Even though it has almost the same meaning as the use of the Ragdup ulos in the experience of the Batak ethnicity in other areas such as Samosir. The research conducted shows that the desire of the Batak ethnic group to have offspring related to the number of village people is very firm. The offspring in question are generations that are sustainable in the harmony of family and society. The use of the mangiring type of ulos illustrates the desire and hope of the descendants of those whose bones are taken to have the next generation.